A review of recent analyses of the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS) - D. Potter; T. Nasserie; L. Tonmyr (Health Promotion and Chronic Disease Prevention in Canada, 2015)
Introduction: The objective of this analysis is to identify, assess the quality and summarize the findings of peer-reviewed articles that used data from the Canadian Incidence Study of Reported Child Abuse and Neglect (CIS) published since November 2011 and data from provincial oversamples of the CIS as well as to illustrate evolving uses of these datasets. Methods: Articles were identified from the Public Health Agency of Canada's data request records tracking access to CIS data and publications produced from that data. At least two raters independently reviewed and appraised the quality of each article. Results: A total of 32 articles were included. Common strengths of articles included clearly stated research aims, appropriate control variables and analyses, sufficient sample sizes, appropriate conclusions and relevance to practice or policy. Common problem areas of articles included unclear definitions for variables and inclusion criteria of cases. Articles frequently measured the associations between maltreatment, child, caregiver, household and agency/referral characteristics and investigative outcomes such as opening cases for ongoing services and placement. Conclusion: Articles using CIS data were rated positively on most quality indicators. Researchers have recently focussed on inadequately studied categories of maltreatment (exposure to intimate partner violence [IPV]), neglect and emotional maltreatment) and examined factors specific to First Nations children. Data from the CIS oversamples have been underutilized. The use of multivariate analysis techniques has increased.